Pelatihan Pembuatan Aneka Produk dari Bahan Akrilik di Desa Sumber Makmur Kecamatan Tapung Kabupaten Kampar-Riau - SOVIYANTI, EFRITA; LUBIS, NURHAYANI (Komunitas Manajemen Kompetitif, 2017)
Communities in the prosperous village of the tapung sub-district, Riau kampar district, have the main income from the oil palm plantation. At present the age of planting of oil palm they have reached 25 years, that means the oil palm will be felled and planted with new trees, Society will lose its main source of income.Thus, other sources of income are needed to become an additional source of income for them. The problem that arises especially for youth and mother in pengajian in the area is the absence of their skills in producing a product that has economic value.This dedication will provide skill training in making various products from acrylic materials especially for members of the female youth group and mother group of mothers who are members of the study so that they have the ability to produce products of acrylic materialThe plan of activities to be undertaken is first to provide knowledge about various forms of acrylic including the designation of the material, then the training of making products from such materials such as key chains, flowers and bags made from acrylic. The last will be given a little knowledge about the way of marketing of the product. Keywords: Acrylic Product, Entrepreneurship Training, Housewives